2004
DOI: 10.1149/1.1809576
|View full text |Cite
|
Sign up to set email alerts
|

PEALD of a Ruthenium Adhesion Layer for Copper Interconnects

Abstract: Ruthenium thin films were produced by plasma-enhanced atomic layer deposition ͑PEALD͒ using an alternating supply of bis͑ethylcyclopentadienyl͒ruthenium ͓Ru͑EtCp) 2 ] and NH 3 plasma at a deposition temperature of 270°C. The film thickness per cycle was self-limited at 0.038 nm/cycle, which was thinner than the thickness obtained from the conventional ALD using oxygen instead of NH 3 plasma. The ruthenium thin film prepared with PEALD had a preferential orientation toward ͑002͒, and it was progressively promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 17 publications
5
65
2
Order By: Relevance
“…It has been reported that, for some materials and applications, plasma-assisted ALD affords better material properties than thermal ALD in terms of, for example, film density, 166,167,187,207,214,227,228 impurity content, 120,162,229,241,245,271,290,294 and electronic properties. 30,31,50,68,134,135,154,207,208,211,228,229,242,272,290,294,319 In most cases, these improved material properties are a result of the high reactivity provided by the plasma, which will be addressed in more detail below.…”
Section: A Improved Materials Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that, for some materials and applications, plasma-assisted ALD affords better material properties than thermal ALD in terms of, for example, film density, 166,167,187,207,214,227,228 impurity content, 120,162,229,241,245,271,290,294 and electronic properties. 30,31,50,68,134,135,154,207,208,211,228,229,242,272,290,294,319 In most cases, these improved material properties are a result of the high reactivity provided by the plasma, which will be addressed in more detail below.…”
Section: A Improved Materials Propertiesmentioning
confidence: 99%
“…The high plasma reactivity is also beneficial in particular cases where the nucleation delay is shorter for plasma-assisted ALD than for the equivalent thermal ALD process. 31,164,166,168,169,173,179,183 This aspect also contributes to an increased throughput of ALD reactors.…”
Section: E Increased Growth Ratementioning
confidence: 99%
See 2 more Smart Citations
“…Cu thin films fabricated using ALD techniques have poor interfacial adhesion to oxide dielectrics, such as SiO 2 , causing failure of the copper interconnect system. [26][27][28] To evaluate the interfacial adhesion of Cu-Al (4.6 at. %) alloy films and reference Cu-Mn (4.7 at.…”
Section: A131-3 Parkmentioning
confidence: 99%